Antimicrobial Activity of a Bioemulsifier Produced by Serratia marcescens S10 - Ahmed, Entissar Faroun; Hassan, Shatha Salman (Al-Nahrain Journal of Science, 2013)
This study was designed to evaluate the ability of bioemulsifier to inhibit the growth of some pathogenic microorganisms. Fourteen isolates belonged to Serratia sp. were collected and tested for their ability to produce bioemulsifier. Results showed that Serratia marcescens S10 (isolated from the gut of the American cockroach) had the highest ability to produce bioemulsifier, among 14 isolates belong to Serratia spp. and it had the ability to inhibit the growth of some microorganisms. The production of bioemulsifier was detected by determination of emulsification index (E24%), qualitative drop-collapse test, emulsification activity (E.A) and measuring the surface tension (S.T). The results of bioemulsifier produced by Serratia marcescens S10 cultivated in mineral salts broth containing olive oil were: E24%= 87%, E.A= 0.31 and reducing of surface tension from 65mN/m to 41.5mN/m. The bioemulsuifier was extracted by organic solvent (chloroform-methanol and diethylether) and antimicrobial activity (antibacterial and antifungal) of bioemulsifier was tested against some pathogenic microorganisms. Results revealed that bioemulsifier reduced the growth of bacteria (Lesteria spp., Salmonella spp., Klebsiella spp. and Staphylococcus aureus) and inhibited the growth of fungi (Candida albicans, Aspergillus niger and Geotricum spp.).